Free the press the death of American journalism and how to revive it - Karem, Brian J. (Prometheus, 2021)
"Blending his experiences as a veteran reporter with trenchant analysis of the erosion of trust between the press and the government in the past 40 years, Free the Press gives readers a unique perspective on the challenges facing journalism, as well as the rise of hostility between these institutions"--